BIODEGRADATION ENHANCEMENT OF OILY WASTEWATER BY OZONATION METHOD - Syafrizal Syafrizal; Zulkifliani Zulkifliani; Fami Adetyas Maulana Pratama; Setijo Bismo (Testing Center for Oil and Gas LEMIGAS, 2015)
This research is aimed at improving the ability of oily wastewater biodegradation through the ozonation method, where ozone will oxidize organic compounds in the oily wastewater that are diffi cult to be degraded by bacteria so that the structure becomes simpler. The ozonation process is done by using a corona-discharge ozonator and semi-batch reactor, and the process is varied by ozone dose and pH value. The ozonation process is then followed by a biodegradation process, where the bacteria that is used is Pseudomonas sp. This study also observed the effect of surfactants in supporting the biodegradation processes. An indicator of research success is the increase in the biodegradation percentage of the sample, followed by an increase in the value of the constant rate of bacterial growth. The research results shows that the ozonation method and the use of surfactant can support the oily wastewater biodegradation process. This is shown by the value of the biodegradation percentage and the constant rate of bacterial growth results, in which respective values are able to reach 86,787% and 0,339 at the optimal operating conditions (ozone dose of 0.53 g/h; pH 7; Bios-H surfactant concentration 500 ppm).